2005
DOI: 10.4321/s1130-01082005001000004
|View full text |Cite
|
Sign up to set email alerts
|

Acute appendicitis in an incarcerated crural hernia: analysis of our experience

Abstract: Introduction: the finding of the vermiform appendix within a crural hernia (Amyand's hernia) is a rare entity whose incidence is not described in the literature. Objective: the aim of this study was to report our hospital's experience in this kind of pathology. Material and methods: between 1993 and 2004, 4,572 acute appendicitis and 372 incarcerated crural hernia cases have been operated on in our hospital. We studied 6 cases of incarcerated crural hernia with vermiform appendix inside. We analyzed in retrosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
35
0
5

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 7 publications
0
35
0
5
Order By: Relevance
“…Contrary to appen- dicitis which is rare in neonates, most cases of Amyand's hernia have been reported in premature neonates, infants and postmenopausal women. Majority of cases present as obstructed or strangulated inguinal hernia and even with perforation with generalized peritonitis, systemic signs and symptoms of appendicitis are rarely evident [3][4][5]. In our case the neonate presented with features of irreducible hernia and in spite of underlying gangrene of appendix, the features of bowel strangulation were completely masked.…”
Section: Discussionmentioning
confidence: 77%
“…Contrary to appen- dicitis which is rare in neonates, most cases of Amyand's hernia have been reported in premature neonates, infants and postmenopausal women. Majority of cases present as obstructed or strangulated inguinal hernia and even with perforation with generalized peritonitis, systemic signs and symptoms of appendicitis are rarely evident [3][4][5]. In our case the neonate presented with features of irreducible hernia and in spite of underlying gangrene of appendix, the features of bowel strangulation were completely masked.…”
Section: Discussionmentioning
confidence: 77%
“…5 Solecki et al observed that acute appendicitis was found in 0.62% of groin hernia sac. 6,7 Gurer et al has reported that appendix was found in 0.51 %, and acute appendicitis was found in 0.1 % of groin hernia sac. 8,9 Amyand hernia usually occurs on the right side, probably as a consequence of normal anatomic position of the appendix.…”
Section: Discussionmentioning
confidence: 97%
“…Fem- oral hernias are the second most common type, often called the DeGarengeot hernia, and they are most commonly found in postmenopausal females. 4,11 Although inflammation of the appendix in its usual anatomical position is caused by obstruction of the lumen by a fecalith, inflammation in an Amyand hernia is thought to be caused by 1 of 2 mechanisms. The first is a primary inflammatory process that causes edema to the surrounding structures, including the internal ring resulting in incarceration and obstruction.…”
Section: Discussionmentioning
confidence: 98%
“…4,5 Roughly only 0.1% of inguinal hernias contain an inflamed appendix. [6][7][8] This incidence is as high 16.6% in 1 series, including only children.…”
Section: Discussionmentioning
confidence: 99%